Hydrogen sulfide donor AP123 restores endothelial nitric oxide-dependent vascular function in hyperglycemia via a CREB-dependent pathway - Rosangela Montanaro; Valentina Vellecco; Roberta Torregrossa; Gian Marco Casillo; Onorina Laura Manzo; Emma Mitidieri; Mariarosaria Bucci; Sigismondo Castaldo; Raffaella Sorrentino; Matthew Whiteman; Martina Smimmo; Flavia Carriero; et al. (Redox Biology, 2023)
Diabetes is associated with severe vascular complications involving the impairment of endothelial nitric oxide synthase (eNOS) as well as cystathionine γ-lyase (CSE) activity. eNOS function is suppressed in hyperglycaemic conditions, resulting in reduced NO bioavailability, which is paralleled by reduced levels of hydrogen sulfide (H2S). Here we have addressed the molecular basis of the interplay between the eNOS and CSE pathways. We tested the impact of H2S replacement by using the mitochondrial-targeted H2S donor AP123 in isolated vessels and cultured endothelial cells in high glucose (HG) environment, at concentrations not causing any vasoactive effect per se. Aorta exposed to HG displayed a marked reduction of acetylcholine (Ach)-induced vasorelaxation that was restored by the addition of AP123 (10 nM). In HG condition, bovine aortic endothelial cells (BAEC) showed reduced NO levels, downregulation of eNOS expression, and suppression of CREB activation (p-CREB). Similar results were obtained by treating BAEC with propargylglycine (PAG), an inhibitor of CSE. AP123 treatment rescued eNOS expression, as well as NO levels, and restored p-CREB expression in both the HG environment and the presence of PAG. This effect was mediated by a PI3K-dependent activity since wortmannin (PI3K inhibitor) blunted the rescuing effects operated by the H2S donor. Experiments performed in the aorta of CSE−/− mice confirmed that reduced levels of H2S not only negatively affect the CREB pathway but also impair Ach-induced vasodilation, significantly ameliorated by AP123. We have demonstrated that the endothelial dysfunction due to HG involves H2S/PI3K/CREB/eNOS route, thus highlighting a novel aspect of the H2S/NO interplay in the vasoactive response.